2020
DOI: 10.32682/sastranesia.v8i2.1453
|View full text |Cite
|
Sign up to set email alerts
|

Perlawanan Ketidakadilan Gender Pada Naskah Drama Pelacur Dan Presiden Karya Ratna Sarumpet

Abstract: Penelitian ini dilakukan bertujuan utuk mengetahui bentuk ketidakadilan gender dan bentuk perlawanan perempuan pada naskah drama yang berjudul Pelacur dan Presiden karya Ratna Sarumpet. Untuk memecahkan permasalahan-permasalahan yanbg ada dalam naskah drama tersebut digunakan teori feminisme liberal Mary Wollstonecraft. Penelitian ini menggunakan pendekatan feminisme. Sumber data untuk penelitian ini adalah naskah drama Perempuan dan Presiden karya Ratna Sarumpet. Proses pengumpulan data dilakukan deng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The other social facts were shown by Suhendi (2014), such as female marginalization and physical-psychological acts of violence. Studies by Fahmi & Arfiyanti (2020), Mahdalia & Qur'ani (2020), and Pratama et al (2020) also found the physical and psychological violence experienced by the female characters. Females were underestimated and there were gender inequalities inside of the patriarchal community.…”
Section: Introductionmentioning
confidence: 94%
“…The other social facts were shown by Suhendi (2014), such as female marginalization and physical-psychological acts of violence. Studies by Fahmi & Arfiyanti (2020), Mahdalia & Qur'ani (2020), and Pratama et al (2020) also found the physical and psychological violence experienced by the female characters. Females were underestimated and there were gender inequalities inside of the patriarchal community.…”
Section: Introductionmentioning
confidence: 94%